Model Pendampingan Ritual Fua Tulu di Gereja Sesawi Oekamusa Fua Tulu Ritual Accompaniment at Sesawi Oekamusa Curch - Riana S. C. Banoet; Jopie D. Engel; Ebenhaizer I. Nuban Timo (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This study aims are to describe and analyse the important value of Fua Tulu Ceremonial for the Society.  This value produce an efficient ritual accompaniment, starting from congregation guilding in Sesawi Oekamusa curch as a part of Mnelalete citizens. The method were used is qualitative approach in which be described. This study applies the development of qualitative research methods and library research. Collecting data is done by interview, observation and theoretical review. The result and discussion of this paper describe and analyze the important social values in this ritual for the community. This exploration can be an effective accompaniment model to improving the communities self confidence, not only of their own personality strength, but also of their environment potency, utilize the togetherness trait of congregation. It is valuable for such positive behavioral, from pessimistic and hopeless sensivity to optimistic and hopefull personal. The curch and also other kind of partnership be recommended to use Fua Tulu accompaniment.  The advance of Fua Tulu as pastoral support could be the strengthness of the curch to addresse the agriculture matters and also to prevent other problems. The author recommends to other researcher to complement this kind of ritual accompaniment.